Measuring the Quality of Accounting Information in the Face of with Employer Loyalty with Approach PSO Algorithm - ZAKIZADEH, ABBAS; KHERADYAR, SINA; NODEH, FAZEL MOHAMMADI; MOUSAABAD, AIYOUB AHMADI (The journal of contemporary issues in business and government, 2021)
Employer loyalty stems from a positive attitude towards a service that is directly related to the working relationship between the auditor and the Employer. This may be due to a better working relationship with the auditor of your choice or an opportunity to influence the auditor. Managers may seek auditing to approve the method because they do not prepare financial statements in accordance with common accounting principles. In this case, the level of quality of accounting information largely depends on the behavior of managers. The present study tries to optimize the quality of accounting information in the face of customer loyalty by using the algorithm (PSO) in a period of 7 years from 2012 to 2018. The results showed that in each group of loyalty and loyalty of the Employer, the number of characteristics with equal desirable and undesirable levels is equal and in Tehran Stock Exchange, managers, whether loyal to their previous auditor or not, the highest level of importance and desirability can be attributed to the characteristic They give confidence and give the lowest level of relevance.